Procedings of the British Machine Vision Conference 2015 2015
DOI: 10.5244/c.29.171
|View full text |Cite
|
Sign up to set email alerts
|

Semantic description of medical image findings: structured learning approach

Abstract: Computer Aided Diagnosis (CADx) systems are designed to assist doctors in medical image interpretation. However, a CADx is often thought of as a "black box" whose diagnostic decision is not intelligible to a radiologist. Therefore, a system that uses semantic image interpretation, and mimics human image analysis, has clear benefits. In this paper, we propose a system which automatically generates textual description of medical image findings, such as lesions.Having found a lesion, a radiologist examines its vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The The classification results show that our second stage properly infers the tumor shape from the binary mask of the breast tumor, which was obtained from the first stage (cGAN segmentation). Hence, we have empirically shown that our CNN is focusing its learning on the morphological structure of the breast tumor, while the rest of approaches ( [10], [11], [45], [46]) rely on the original pixel variations of the input mammogram to make the same inference. Moreover, in [32] they used a hybrid strategy in which they include the pixel variability within the mask of breast tumor region to retain the intensity and texture information.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The The classification results show that our second stage properly infers the tumor shape from the binary mask of the breast tumor, which was obtained from the first stage (cGAN segmentation). Hence, we have empirically shown that our CNN is focusing its learning on the morphological structure of the breast tumor, while the rest of approaches ( [10], [11], [45], [46]) rely on the original pixel variations of the input mammogram to make the same inference. Moreover, in [32] they used a hybrid strategy in which they include the pixel variability within the mask of breast tumor region to retain the intensity and texture information.…”
Section: Resultsmentioning
confidence: 99%
“…For a quantitative comparison, we compared our model with three state-of-the-art tumor shape classification methods [12,10,11]. The three methods were evaluated on the DDSM dataset.…”
Section: Shape Classification Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative features are derived by applying advanced mathematical algorithms to the images (as in the case of radiomics). 2,21,22 Semantic and quantitative features can be used in statistical or artificial intelligence (AI) models to predict specific clinical endpoints. Individual radiomic features can be combined to form imaging 'signatures' or 'phenotypes'.…”
Section: Imaging Featuresmentioning
confidence: 99%